2007
DOI: 10.1099/vir.0.82487-0
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ regulates human immunodeficiency virus 1 gene expression through its association with cdk9

Abstract: Transcriptional regulation of the human immunodeficiency virus type 1 (HIV-1) is a complex event that requires the cooperative action of both viral (e.g. Tat) and cellular (e.g. C/EBPβ, NF-κB) factors. The HIV-1 Tat protein recruits the human positive transcription elongation factor P-TEFb, consisting of cdk9 and cyclin T1, to the HIV-1 transactivation response (TAR) region. In the absence of TAR, Tat activates the HIV-1 long terminal repeat (LTR) through its association with several cellular factors including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…In addition, Tat increased the expression of C/EBPb and C/EBPd, two transcription factors that play a pivotal role in the early steps of adipogenesis. The linkage between Tat and the C/EBP family factors has already been described in other cellular targets than MSCs [Liu et al, 2002;Mameli et al, 2007]. Tat induced C/EBPb expression and cooperated in LTR promoter modulation with C/EBP family members to increase the HIV transcription [Liu et al, 2002].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, Tat increased the expression of C/EBPb and C/EBPd, two transcription factors that play a pivotal role in the early steps of adipogenesis. The linkage between Tat and the C/EBP family factors has already been described in other cellular targets than MSCs [Liu et al, 2002;Mameli et al, 2007]. Tat induced C/EBPb expression and cooperated in LTR promoter modulation with C/EBP family members to increase the HIV transcription [Liu et al, 2002].…”
Section: Discussionmentioning
confidence: 93%
“…The JCV E -CAT promoter mutants m1 and m2 were made by site-directed mutagenesis using the QuickChange II XL Site-Directed Mutagenesis Kit (Stratagene, La Jolla, CA) with double stranded oligonucleotides with the sequences 5’-aaaaacaactcaatttccctggcctcc-3’ and 5’-aaaaacaagggactctccctggcctcc-3’ respectively. The expression plasmids pCMV-p65, pCMV-CHOP and pCMV-C/EBPβ were described previously (Gorrill and Khalili, 2005; Mameli et al, 2007). pCMV-LIP and pCMV-LAP were kindly provided by Dr. Ueli Schibler, University of Geneva.…”
Section: Methodsmentioning
confidence: 99%
“…It is tempting to speculate that the DS1 site may be involved in mediating Tat transactivation and productive virus replication perhaps by tethering and stabilizing Tat binding to the TAR element. Tat has been shown to increase expression of the C/EBP␤ protein and binding of C/EBP␤ to DNA in vitro (55), in addition to physically and functionally interacting (in vitro and in vivo) with C/EBP␤ to induce interleukin 6 and MCP-1 (monocyte chemoattractant protein 1 or CCL2 (55)(56)(57)(58)). Moreover, Mameli et al (58) demonstrated that the Tat-C/EBP␤ functional and physical association is mediated through cyclin T1/cdk9 in U-87MG astrocytic cells and possibly influences cates in perivascular macrophages, and spreads to resident macrophages (1,2,8,69).…”
Section: Discussionmentioning
confidence: 99%